Treatment of an Intractable Forefoot Ulcer Using Realignment Osteotomy in a Patient with Rheumatoid Arthritis - Makoto Imai; Naoki Kondo; Rei Kumazaki; Naoto Endo (Case Reports in Orthopedics)
Forefoot deformities are common among patients with rheumatoid arthritis (RA). Herein, we describe a case of intractable ulceration on the dorsomedial aspect of the right 5th digit, secondary to forefoot deformity, in a 76-year-old woman with a 35-year history of RA. The ulcer was due to a persistent subcutaneous infection. Although the infection was controllable with antibiotics, there was concern of relapse because of the abnormal pressure on the skin due to an overlap of the 4th and 5th digits. We proceeded with surgical correction of the forefoot alignment, including shortening oblique osteotomy of metatarsals 2 through 5, rather than amputation of the 5th digit. Following surgery, targeted antibiotic treatment was provided. The postoperative course was unremarkable, and the patient recovered weight-bearing function without recurrence of pain or ulceration. Forefoot realignment is a feasible option that should be considered for treating intractable foot pain and ulceration secondary to long-lasting RA.